Determinan faktor sosial dan lingkungan terhadap balita stunting di Sumatera Selatan: SKI 2023 - Agustina, Dwi Putri; Mutahar, Rini (Holistik Jurnal Kesehatan, 2025)
Background: Stunting is a health problem that has long-term impacts on children's quality of life. Social and environmental factors are suspected to play an important role in the occurrence of stunting. Purpose: To analyze social and environmental factors on stunting in toddlers in South Sumatra. Method: This research uses a cross-sectional study design with secondary data analysis from the 2023 Indonesian Health Survey. The sample consists of 10,120 children aged 0-59 months. The variables examined include gender, maternal education, place of residence, drinking water quality, and sanitation. Data analysis was conducted using univariate, bivariate, and multivariate logistic regression. Results: Factors significantly related to stunting incidence are child gender (p=0.000), mother's education (p=0.000), sanitation (p=0.000), and place of residence (p=0.000). Meanwhile, drinking water quality did not show a significant relationship with stunting incidence (p=0.070). Conclusion: Efforts to prevent stunting need to focus on increasing maternal education, improving sanitation, and increasing access to health services in rural areas.   Keywords: Environment; Social; Stunting.   Pendahuluan: Stunting merupakan masalah kesehatan yang berdampak jangka panjang terhadap kualitas hidup anak, Faktor sosial dan lingkungan diduga memiliki peran penting dalam kejadian stunting. Tujuan: Untuk menganalisis faktor sosial dan lingkungan terhadap balita stunting di Sumatera Selatan. Metode: Penelitian ini menggunakan desain studi cross-sectional dengan analisis data sekunder dari Survei Kesehatan Indonesia (SKI) 2023. Sampel terdiri dari 10,120 balita usia 0-59 bulan. Variabel yang dikaji meliputi jenis kelamin, pendidikan ibu, tempat tinggal, kualitas air minum, dan sanitasi. Analisis data dilakukan secara univariat, bivariat, dan multivariat menggunakan regresi logistik. Hasil: Faktor yang berhubungan signifikan dengan kejadian stunting adalah jenis kelamin anak (p=0.000), pendidikan ibu (p=0.000), sanitasi (p=0.000), dan tempat tinggal (p=0.000). Sementara itu, kualitas air minum tidak menunjukkan hubungan signifikan dengan kejadian stunting (p=0,.070). Simpulan: Upaya pencegahan stunting perlu difokuskan pada peningkatan pendidikan ibu, perbaikan sanitasi, dan peningkatan akses layanan kesehatan di daerah perdesaan.   Kata Kunci: Lingkungan; Sosial; Stunting.